100 days of Muhyiddin’s Government leadership: a manifestation of the continuity of paternalism values - Jaes, Lutfan; Razali, Nurul Aimi; Mohd Yusof, Asyraf Maula; Mohd Suhaimyd, Khairul Azman (2021)
This article attempts to describe Muhyiddin in leading the Pakatan Nasional Government (PN), especially in the era of Covid-19 pandemic management. It is traced through the role of Asian Values which are believed to shape the leadership character in his administration as the 8th Prime Minister of Malaysia. The stance on values and dimensions was referred based on the highlights of past literatures which stated that Asian countries have their own set of unique ideologies. It was then developed through the observation of one hundred (100) days of Muhyiddin’s administration. Content analysis was applied as a research design aimed at identifying and then describing his significant speech text passages. The analysis looks at Paternalistic Leadership in the tendencies of “Work Ethics”, “Society”, “Power Orientation”, and “Family” value dimensions. These four dimensions are often discussed by scholars in underlying the leadership style of Asian leaders. Data encoding was performed using the ATLAS software. The results show that Muhyiddin has indeed applied paternal values in governing. He managed to incorporate these values indirectly in the local wisdom of the community by manipulating those values by adapting to current needs. Muhyiddin does so with the soothing values of paternalism while shaping the development of the country more pragmatically and effectively. In conclusion, the restoration of the local wisdom values has become a factor driving the significant progress of Malaysia’s post-PH Government continuous development.